Creation and Validation of the Japanese Cute Infant Face (JCIF) Dataset - Nittono, Hiroshi; Ohashi, Akane; Komori, Masashi (Frontiers in Psychology, 2022)
Research interest in cuteness perception and its effects on subsequent behavior and physiological responses has recently been increasing. The purpose of the present study was to produce a dataset of Japanese infant faces that are free of portrait rights and can be used for cuteness research. A total of 80 original facial images of 6-month-old infants were collected from their parents. The cuteness level of each picture was rated on a 7-point scale by 200 Japanese people (100 men and 100 women in their 20s to 60s). Prototypical high- and low-cuteness faces were created by averaging the top 10 and bottom 10 faces according to the mean cuteness ratings. Then, 50 composite faces were made by mixing two faces randomly chosen from the 60 unused middle-cuteness faces. The normative cuteness ratings of these composite faces were obtained from 229 Japanese men and women in their 20s to 60s. The shape of each composite face was transformed to be cuter (+50%) or less cute (–50%) along a continuum between the high- and low-cuteness prototypical faces. A two-alternative forced-choice task (N = 587) confirmed that cuteness discrimination was better than the chance level for all 50 face pairs. Moreover, the results showed that young men had poorer sensitivity to cuteness differences in infant faces than older men and women of any age. This Japanese Cute Infant Face (JCIF, “jay-sif”) dataset, including composite face images and normative rating scores, is publicly available online.